THE INFLUENCE OF CLASSROOM CONDITIONS ON THE EFFECTIVENESS OF STUDENT LEARNING IN SOCIAL SCIENCES SUBJECTS IN CLASS VIII OF DARUL KIROM ISLAMIC MIDDLE SCHOOL JATISAMPURNA - Siti Fathonah; Ismeirita _ (Jurnal Ilmu Pendidikan Ahlussunnah, 2023)
The Influence of Classroom Conditions on the Effectiveness of Student Learning in Social Sciences Subjects in Class VIII of Darul Kirom Islamic Middle School Jatisampurna (2023). Bekasi. Panca Sakti University. 2023. The aim of this research is to understand the influence of classroom conditions on the learning effectiveness of class VIII students in social studies subjects at Darul Kirom Jatisampurna Islamic Middle School. To obtain data, a classroom condition instrument and a learning effectiveness instrument were used in the form of a Likert scale model. This research utilized a quantitative approach, with data sources obtained from a population of 137 students, with a sample size of 58 class VIII students at Darul Kirom Islamic Middle School. Sampling technique by means random sampling. The data examination procedure used is simple linear regression using SPSS (Statistical Product and Service Solution) version 20.0 Windows. The results of data analysis prove that classroom conditions have a direct effect on student learning effectiveness by 15.2%. The remaining 84.8% was influenced by other factors not examined in this research. So the condition of the classroom here is one of the crucial factors that must be focused on in order to achieve effective learning success.